Exploring the views of patients' and their family about patient‐initiated follow‐up in head and neck cancer: A mixed methods study. (4th July 2022) - Lorenc, Ava; Greaves, Colin; Duda, Joan; Brett, Jo; Matheson, Lauren; Fulton‐Lieuw, Tessa; Secher, Denis; Rhodes, Pat; Ozakinci, Gozde; Nankivell, Paul; Mehanna, Hisham; Jepson, Marcus; et al.
Abstract: Objective: The objective of this work was to explore head and neck cancer (HNC) patients' and their family members' views on acceptability and feasibility of patient‐initiated follow‐up (PIFU), including concerns and anticipated benefits. Methods: Patients were recruited from UK HNC clinics, support groups and advocacy groups. They completed a survey ( n  = 144) and/or qualitative interview ( n  = 30), three with a family member. Qualitative data were analysed thematically, quantitative data using descriptive statistics. Results: Preference for follow‐up care in HNC was complex and individual. Many patients thought PIFU could beneficially reallocate health care resources and encourage self‐management. Patients' main concerns with PIFU were losing the reassurance of regular clinic appointments and addressing mental well‐being needs within PIFU, possibly using peer support. Patients were concerned about their ability to detect recurrence due to lack of expertise and information. They emphasised the importance of a reliable, direct and easy urgent appointment service and of feeling supported and heard by clinicians. Patients believed family and friends need support. Conclusion: PIFU may be feasible and acceptable for certain HNC patients, providing it addresses support for mental well‐being, provides quick, reliable and direct clinician access and information on "red flag" symptoms, and ensures patients and their caregivers feel supported.